STRATEGI GURU PAI DALAM PEMBELAJARAN PRAKTIK SHALAT PADA ANAK BERKETUNAAN TUNARUNGU - Nur Aini Fatimah; Hartati, Zainap; Sapuadi , Sapuadi (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to describe the strategies used by Islamic Education (PAI) teachers in teaching prayer practices to deaf students in grade X at SKH Negeri 1 Palangka Raya. The background of this study is based on the need for adaptive learning for deaf students who have difficulty receiving verbal information, thus requiring a visual approach and methods that are appropriate to their characteristics. The method used in this study is descriptive qualitative through data collection techniques such as observation, interviews, and documentation. The results of the study indicate that PAI teachers employ teaching strategies that emphasize the use of visual media, hands-on practice, and adapting materials to students' abilities. The methods used in teaching include lectures, writing materials on an interactive TV, videos, images, and simple sign language. Evaluation was conducted gradually through direct observation of students' prayer practices. Challenges faced include limitations in teachers' mastery of sign language and a shortage of assistant teachers, while solutions implemented include the use of simple sign language, visual media, and individual guidance. These strategies align with the principles of inclusive education and differentiated learning, but still require improvements in teachers' competencies and resource support.